2017
DOI: 10.1194/jlr.m068387
|View full text |Cite
|
Sign up to set email alerts
|

Lifelong imbalanced LA/ALA intake impairs emotional and cognitive behavior via changes in brain endocannabinoid system

Abstract: Imbalanced dietary n-3 and n-6 PUFA content has been associated with a number of neurological conditions. Endocannabinoids are n-6 PUFA derivatives, whose brain concentrations are sensitive to modifications of fatty acid composition of the diet and play a central role in the regulation of mood and cognition. As such, the endocannabinoid system appears to be an ideal candidate for mediating the effects of dietary fatty acids on mood and cognition. Lifelong administration of isocaloric α-linolenic acid (ALA)-def… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 62 publications
(75 reference statements)
0
16
0
Order By: Relevance
“…NAEs were extracted from brain areas and plasma and then quantified as previously reported . In brief, plasma and brain areas were dounce‐homogenized and extracted with chloroform/methanol/Tris‐HCl (50 mM, pH 7.4) (2:1:1, v/v) containing internal deuterated standards for PEA, OEA, AEA, and DHEA quantification by isotope dilution [d4‐PEA, d4‐OEA, d8‐AEA, and d4‐DHAEA (Cayman Chemical)], as well as 17:0‐AE (Cayman Chemical) for EPEA measurement.…”
Section: Methodsmentioning
confidence: 99%
“…NAEs were extracted from brain areas and plasma and then quantified as previously reported . In brief, plasma and brain areas were dounce‐homogenized and extracted with chloroform/methanol/Tris‐HCl (50 mM, pH 7.4) (2:1:1, v/v) containing internal deuterated standards for PEA, OEA, AEA, and DHEA quantification by isotope dilution [d4‐PEA, d4‐OEA, d8‐AEA, and d4‐DHAEA (Cayman Chemical)], as well as 17:0‐AE (Cayman Chemical) for EPEA measurement.…”
Section: Methodsmentioning
confidence: 99%
“…Since n-6 series-derived eicosanoids are associated with proinflammatory properties, the predominance of n-6 PUFA is suggestive of higher risks of childhood allergic diseases, such as asthma and atopic eczema (9,15) . Also, the imbalance between n-6 and n-3 PUFA has been correlated with impaired cognitive and emotional development via epoxy metabolites and endocannabinoid system (12,13,36) . More investigations are warranted to confirm whether the increasing ratio of LA:ALA or n-6:n-3 PUFA in human milk is harmful to the short-term and long-term health of human infants.…”
Section: Fatty Acidsmentioning
confidence: 99%
“…balance and neocortical development (9,12,13) . Contrarily, n-3 LC-PUFA help in promoting psychomotor development and lowering the risk of lifelong allergic diseases and emotional problems (8,12,14,15) .…”
mentioning
confidence: 99%
“…14,30 Moreover, many desaturase genes participate in the synthesis of u-3 LC-PUFAs from the precursor essential PUFAs, 31 such as LA and ALA, which share the same enzyme system. 16,32 Our data demonstrated that the expression of lipogenic enzymes could be affected by different dietary levels of ALA (Fig. 3).…”
Section: Discussionmentioning
confidence: 57%